Applying Ubuntu-Botho African ethics to stakeholder corporate social responsibility. (17th November 2014) - Gonçalves das Neves, José; Patrícia Duarte, Ana; Simões, Eduardo; Mofuoa, Khali
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore, with the view to establish the prospects of applying Ubuntu-Botho African approach to stakeholder corporate social responsibility (CSR) for business organisations in sub-Saharan Africa (SSA), the experience of Basotho of Lesotho in using Ubuntu-Botho African principles and practices to pursue their socially responsible development fashioned in social responsibility (SR) terms. Design/methodology/approach – Using data mainly from desktop research, the theoretical or conceptual content of the paper was established to inform the discussions on the prospects of applying Ubuntu-Botho African principles and practices to stakeholder CSR for business organisations in SSA. Findings – Ubuntu-Botho African approach to stakeholder CSR could generate a very different notion of ideal SR of business organizations in the context of SSA as the experience of Basotho of Lesotho reveals. Whether or not one is persuaded by this Ubuntu-Botho approach to stakeholder CSR, the discussion serves to illuminate the need to broaden the terms of the debate over the appropriate role of business organizations, at least in the context of SSA, regarding their CSR and performance within which they operate. Originality/value – The paper mainly uses secondary data that is considered to be most relevant, valid and reliable to inform discussions on the prospects of the application of Ubuntu-Botho African ethics to stakeholder CSR for business organisations in the context of SSA. The author's knowledge of Lesotho – where he lived, studied and worked – informed the writing of this paper, as well as discussions on the prospects of applying Ubuntu-Botho African approach to stakeholder CSR for business organisations in SSA using the experience of Basotho of Lesotho in engineering their socially responsible development to become the granary of Southern Africa in 1900s.